Estimating a monetary policy reaction function for the Dominican Republic - José R. Sánchez-Fung (University of Kent, Department of Economics, 2002)
This paper specifies and estimates a hybrid monetary policy base reaction function for the Dominican Republic (DR). The estimated reactions suggest that the Central Bank has been biased towards targeting the gap between the parallel and official exchange rates, apparently doing so in a more systematic fashion after the mid 1980s. Remarkably, these findings are in line with the Central Bank's long-standing endorsement of a multiple exchange rate regime, and could imply a process of learning, given the monetary authorities' preferences.
Keywords: E52; E58; F41; 330; monetary policy base reaction function; multiple exchange rates market; dynamic modelling; Dominican Republic; Geldpolitik; Theorie; Dominikanische Republik; Multipler Wechselkurs; Ökonometrisches Modell